UTHM Shuttle Bus Application: UTHM Shuttle Bus Application - Adnan, Nur Syuhada Idayu; hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2021)
In the rise of information technology, manual routine, system, and activity has turned out to be useless and a waste of time. In Malaysia, the manual system is still working as daily activity where system can replace it. The lack of knowledge and learning was the main factor of the manual system exist and not being replace. The key point of proposing this idea is to build a mobile application for UTHM shuttle bus booking system. Its goal is to convert the manual routine of shuttle bus booking into a computerized system to ease the routine proses. The proposed system will serve as a communication platform between drivers and students. The system will allow user to book a shuttle bus to ride and pick a drop-off destination beforehand. The system will also allow the bus driver to see the list of bus stops they need to pick and drop user. The rides information will be record for internal usage. k.